PERAN NILAI KEISLAMAN TERHADAP KONSEP DASAR MATEMATIKA - Nurfaizah Mutmainah (Sindoro: Cendikia Pendidikan, 2024)
Islamic values ​​have a significant influence on various fields of science, including mathematics. The integration of Islamic values ​​into basic mathematical concepts not only enriches the understanding of the science itself, but also instills spiritual values ​​that can guide students in thinking logically and responsibly. This article aims to examine the influence of Islamic values ​​on basic mathematical concepts, such as logic, numbers, and geometry. Through a theoretical approach and literature analysis, it was found that Islamic values ​​can strengthen the understanding of basic mathematics by emphasizing order, harmony, and moral responsibility in the learning process.